2014
DOI: 10.5539/jas.v6n10p128
|View full text |Cite
|
Sign up to set email alerts
|

Carcass Traits in Sheep Receiving Acacia mearnsii Condensed Tannin Extract to Control Endoparasites

Abstract: We evaluated carcass traits from twenty 6-month-old Santa Ines lambs under tropical grazing (Andropogon gayanus) receiving condensed tannin from Acacia mearnsii once a week for 13 weeks to control endoparasites. Ten animals were treated with tannin (TG) and the remainder (10 animals) received a diet without tannin (CG). At slaughter, the following measurements were taken: live weight, carcass weight, half-carcass weight, carcass length, fat cover, skin weight and thickness, weight of thoracic and abdominal org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…There was only a tendency toward an increased leg weight in VVI lambs ( p = 0.076), which is difficult to explain. Similar results were obtained by Louvandini et al . in lambs receiving an extract from Acacia mearnsii (condensed tannins) in the diet.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…There was only a tendency toward an increased leg weight in VVI lambs ( p = 0.076), which is difficult to explain. Similar results were obtained by Louvandini et al . in lambs receiving an extract from Acacia mearnsii (condensed tannins) in the diet.…”
Section: Discussionsupporting
confidence: 89%
“…The results of this study are consistent with a study Vasta et al., in which condensed tannins from Ceratonia siliqua decreased crude fat content in the MLD in comparison to the control group and animals receiving PEG. Lower fat proportion was shown in lambs fed a diet with Acacia mearnsii extract . The latter authors suggested that the amount of condensed tannins in the diet was positively correlated with growth hormone levels in lambs and may affect lipid metabolism.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation